Enhanced mechanical and tribological performance of additively manufactured 316L steel by MoS2-reinforcement - Sangharatna M. Ramteke; Jorge Ramos Grez; Max Marian (Materials & Design)
316L stainless steel is commonly used in industrial and biomedical applications due to its corrosion resistance and biocompatibility, though its wear resistance is limited. This study aims to enhance the wear performance of 316L using additive manufacturing (AM) via laser powder bed fusion (LPBF), reinforcing it with MoS2 particles. Metal matrix composites (MMCs) were fabricated with MoS2 particles of different combinations in size (1.5, 4.5, 12.5 µm) and concentration (1, 3, 5 wt-%). Increasing MoS2 content reduced the density across all particle sizes due to MoS2′s lower intrinsic density, with smaller particles increasing surface roughness and larger particles reducing roughness variation while enhancing hardness. Notable variations in the coefficient of friction and wear coefficients were observed across different composites and temperatures in a steel ball-on-three-MMC plate setup under dry conditions. At 25 °C, 4.5 µm MoS2 at 5 wt-% reduced MMC plates’ wear by 96.3 % and counter body (steel ball) wear by 85.5 %. At 37 °C, 12.5 µm MoS2 at 1 wt-% reduced plate wear by 97.1 % and ball wear by 91 %. These improvements were attributed to enhanced solid lubrication and load distribution, particularly with optimal MoS2 size and concentration. This research highlights the potential of LPBF-AM in producing high-performance 316L MMCs for applications requiring improved wear resistance.